Cross-currency hedging with multiple options - Buck, Alexander Wolfram (2017)
Financial derivatives are broadly used for hedging purposes by large ﬁnancial and non-ﬁnancial corporations in developed countries. Thereof, currency derivatives represent the biggest class. For some currencies, foreign exchange exposure, for example arising from exports or foreign investments, cannot be hedged due to illiquid or nonexistent derivative markets. However, a third currency with liquid derivative markets exists and can be used to cross-hedge the exposure. This thesis examines whether using options with multiple strikes can improve the hedging performance in such a case. Several stochastic models commonly applied in the literature to foreign exchange markets are used for the out-of-sample hedging portfolio construction and applied to currencies in the regions Latin America, Europe and East/Southeast Asia between 2012 and 2016. This paper delivers two main results: Firstly, it is shown that adding options is not beneﬁcial mainly due to model and estimation errors which increase risk. Secondly, it is shown that if the US-Dollar exchange rate is not cross-hedgeable, the exchange rate with the third currency must be, unless the foreign currency is highly volatile. As a consequence, cross-hedging can be successfully applied to at least one of those exchange rates. However, it is optimal to use only forwards in that case.